Strengthening Student Character through the Practice of Islamic Culture (A Study at MIN 13 Pidie Jaya) - Azizah; Nazaruddin; Saifuddin (PT. Anagata Sembagi Education, 2025)
The cultivation of student character through the integration of Islamic culture in State Elementary Schools (MIN) represents a vital approach to fostering a generation that excels not only academically but also morally. This research seeks to explore the Islamic cultural values implemented at MIN 13 Pidie Jaya and to assess how these values contribute to the enhancement of student character. A qualitative methodology is employed in this study, utilizing data collection methods such as observation, interviews, and document analysis. The findings indicate that the incorporation of Islamic cultural values at Madrasah Ibtidaiyah Negeri (MIN) 13 Pidie Jaya plays a crucial role in the educational process, serving as a conduit for the transmission of traditions and beliefs across generations. The educational focus of this institution extends beyond academic achievement to include the character development of students grounded in Islamic principles. The values promoted encompass respect and ethics, spirituality and worship, as well as moral character traits such as honesty and responsibility. Students are encouraged to engage actively in their communities, appreciate the significance of collaboration, and are recognized for their positive behaviors aligned with Islamic teachings. The daily practices of Islamic culture, including prayer, fasting, and zakat, instill lessons of discipline, responsibility, and respect. Activities such as congregational prayers and collective supplications prior to lessons illustrate the madrasah's dedication to embedding Islamic values into the lives of students. Furthermore, social interactions characterized by mutual respect and sharing, along with initiatives for charity and sacrifice, highlight the importance of social responsibility. The principal and educators play an active role in the implementation of Islamic culture, thereby enriching the educational experiences of students and reinforcing the connection between the school and the broader community.